PENGARUH STRATEGI PEMASARAN DENGAN KONSEP AIDA TERHADAP KEPUTUSAN PEMBELIAN PRODUK PT.WINGS FOOD DI KECAMATAN ALANG-ALANG LEBAR - Santi Oktavianti; Yunita Hasrina (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
This study aims to determine whether the advertising variable according to the AIDA concept has a significant effect on product purchasing decisions of PT. Wings Food and know which AIDA advertising concept variable has the most dominant influence on product purchasing decisions of PT. Wings Food in Alang-Alang Lebar District, using multiple linear regression analysis techniques. The research was conducted by taking a sample of 100 people. Based on the attention variable analysis in advertising based on the AIDA advertising concept with t count (4.606)> t table (1.985) and a probability value of 0.000 <0.05, it has the most dominant influence on consumer purchasing decisions. Wings Food in Alang-alang Lebar sub-district compared to other variables.